Polyvinyl alcohol–collagen–hydroxyapatite composite membrane derived from Lates calcarifer for alveolar socket preservation - Ariesanti, Yessy; Dewi, Imanda Vyatri; Abbas, Basril (Faculty of Dentistry, Universitas Gadjah Mada, 2025)
Alveolar socket preservation (ASP) requires an ideal barrier membrane that provides anti-bacterial activity, water contact angle (WCA) and swelling behavior to support bone regeneration. This study evaluated these characteristics in a Polyvinyl Alcohol-Collagen-Hydroxyapatite composite membranes derived from the scales of Lates calcarifer.L. The PVA-Col-HA CM was produced from the scales of Lates calcarifer through mixing, homogenization, casting, and drying and then divided into three groups: non-irradiated, 15 kGy irradiation, and 25 kGy irradiation. Antibacterial activity was assessed by disk-diffusion test and inhibition zone diameters were measured. Water contact angle was determined using a contact angle goniometer on both membrane surfaces. Swelling behavior was evaluated by immersing samples in phosphate-buffered saline for 60 minutes, followed by periodic weighing and calculation using a swelling formula. The anti-bacterial activity test showed a larger zone of inhibition in the 25 kGy group by 2mm on Escherichia coli and Staphylococcus aureus. One-way ANOVA test of WCA values showed significant differences (p < 0.05) among groups, with the 25 kGy group exhibiting the highest hydrophilicity. Analysis of swelling behavior using ANOVA and Kruskal-wallis test showed no significant differences (p > 0.05) among groups, but the linear graph shows that the 25kGy group displayed the lowest and most stable swelling profile. These findings suggest that the PVA-Col-HA CM exhibited favorable anti-bacterial activity, WCA, and swelling behavior, with optimal performance observed in the 25 kGy irradiation group.